Multi-ethnic marketing: Coca-Cola’s “America Is Beautiful” - Licsandru, Tana Cristina; Cui, Charles Chi (Henry Stewart Talks, 2024)
This case study presents Coca-Cola’s “America is Beautiful” ad as a standout example of purposefully and successfully executed ethnic marketing.